Preparation and characterization of bioactive glass nanoparticles prepared by sol-gel for biomedical applications - Luz, Gisela (2011)
Bioactive glass nanoparticles (BG-NPs), based on both ternary (SiO(2)-CaO-P(2)O(5)) and binary (SiO(2)-CaO) systems, were prepared via an optimized sol-gel method. The pH of preparation and the effect of heat treatment temperature were evaluated, as well as the effect of suppressing P in the bioactivity ability of the materials. The morphology and composition of the BG-NPs were studied using FTIR, XRD and SEM. The bioactive character of these materials was accessed invitro by analyzing the ability for apatite formation onto the surface after being immersed in simulated body fluid (SBF). XRD, EDX and SEM were used to confirm the bioactivity of the materials. The BG-NP effect on cell metabolic activity was assessed by seeding L929 cells with their leachables, proving the non-cytotoxicity of the materials. Finally the most bioactive BG-NPs developed (ternary system prepared at pH11.5 and treated at 700degreesC) were successfully combined with chitosan in the production of biomimetic nanocomposite osteoconductive membranes that could have the potential to be used in guided tissue regeneration.